Control of parallel dry methane and steam methane reforming processes for Fischer–Tropsch syngas. (March 2016) - Luyben, William L.
Highlights: Plantwide control structure developed for two units operating in parallel to produce syngas. Each unit has two fresh feed streams with total methane split to achieve desired combined H2 /CO ratio of product syngas. High-temperature reactors heated by combustion of fuel are effectively modeled using plug-flow tubular reactor models with constant heat flux. Abstract: The ratio of hydrogen to carbon monoxide in the synthesis gas required for feeding to the gas-to-liquid Fischer–Tropsch (FT) process to produce liquid transportation fuel is about two. The dry methane reforming (DMR) process feeds carbon dioxide and methane and produces a syngas with a H2 /CO ratio of about unity. The steam methane reforming (SMR) process feeds water and methane and produces a syngas with a H2 /CO ratio of about four. This paper studies the plantwide control of a process with DMR and SMR units operating in parallel to produce FT syngas. The total methane fresh feed is split between the two parallel processes in the appropriate fraction so as to produce the desired H2 /CO ratio in the mixed syngas stream from the process. Both the SMR and DMR reactions are highly endothermic and the reactors are fired furnaces with combustion of fuel providing the endothermic heat of the reactions. Reactor exit temperatures are controlled by manipulating the flowrates of fuel to each furnace, with combustion air ratioed to the fuel. Dynamic reactor models assume tubular SMR and DMR reactors in which heat fluxes are determined by the heat generated in their associated fuel/air combustion reactors. The plantwide control structure effectively handles large 20% disturbances in throughput and large setpoint changes in the desired H2 /CO ratio (1.7–2.3).